VEGETATIVE PROPAGATION OF SELECTED BALETE SPECIES IN ARGAO, CEBU - Alburo, Hemres M.; Alburo, Rosalyn P.; Pascual, Pet Roey L. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 2, 2015, 2018)
Please see PDF file.